Differential gene expression in the insect vector Anasa tristis in response to symbiont colonization but not infection with a vectored phytopathogen - Mendiola, Sandra Y.; Chen, Jason Z.; Lukubye, Ben; Civitello, David J.; Vega, Nic M.; Gerardo, Nicole M. (Frontiers in Ecology and Evolution, 2024)
Many insects selectively associate with specific microbes in long-term, symbiotic relationships. Maintaining these associations can be vital for the insect hosts' development, but insects must also contend with potential coinfections from other microbes in the environment.Fending off microbial threats while maintaining mutualistic microbes has resulted in many insects developing specialized symbiotic organs to house beneficial microbes. Though locally concentrated in these organs, symbiont establishment can have global consequences for the insect, including influence over the success of coinfecting microbes in colonizing the insect host.We use a transcriptomic approach to examine how the mutualistic symbiosis between the agricultural pest Anasa tristis and bacteria in the genus Caballeronia affects insect gene expression locally within the symbiotic organs and in the insect host at large. We simultaneously determine whether Caballeronia colonization impacts insect host responses to infection with the plant pathogen Serratia marcescens, which it vectors to plants. We found that no significant differential gene expression was elicited by infection with S. marcescens. This was a surprising finding given previous work indicating that symbiotic A. tristis clear S. marcescens infection rapidly compared to aposymbiotic individuals. Our results indicate that symbiotic and nonsymbiotic tissues in A. tristis differ greatly in their gene expression, particularly following successful symbiont colonization. We found evidence for local downregulation of host immunity and upregulation of cell communication within the symbiotic organs, functions which can facilitate the success of the A. tristis-Caballeronia symbiosis.